A new low-loss dielectric material ZnZrTa2O8 for microwave devices. Issue 3 (February 2016) - Lyu, Xiaosong; Li, Lingxia; Zhang, Shuai; Sun, Hao; Li, Sai; Ye, Jing; Zhang, Bowen; Li, Jiangteng
Abstract: The first characterization of the microwave dielectric properties of ZnZrTa2 O8 ceramic is presented. Single phase ZnZrTa2 O8 ceramics with wolframite structure were prepared by a conventional mixed-oxide route and sintered in the temperature range of 1280–1360 °C. The microstructures and microwave dielectric properties were investigated systematically. The variation trend of ε r was in accordance with that of relative density and molecular volume. The Q × f value was mainly depended on the atomic packing fraction. The τf was found to be correlated with the variation of bond valence of the A- and B-site cations. The ZnZrTa2 O8 ceramic sintered at 1320 °C for 6 h exhibited excellent microwave dielectric properties of ε r ∼ 32, Q × f ∼ 110, 700 GHz, and τf ∼ −32 ppm/°C. This constitutes a very promising material for microwave applications.